The Career of Students who Use a Different Language at Home and at School - Zsófia Vincze (Jesuit University Ignatianum in Krakow, 2024)
RESEARCH OBJECTIVE: The objective of the research is to understand how the ethnic composition of the family and the choice of the language of the school are related. THE RESEARCH PROBLEMS AND METHODS: Minorities are often the subject of research, and within, bilingualism, language use arenas and state language education are prominent topics, how‑ ever, the issue of ethnic minority students studying in majority institutions is relatively unexplored. THE PROCESS OF ARGUMENTATION: Our research is focused on the ethnic Hungarian minority in Romania, their decisions and their experiences of education in the majority language. The present qualitative research was carried out in a semi‑structured interview format in November 2023 with 14 respondents, reached by snowball method. RESEARCH RESULTS: Our results show that, in addition to proximity to the institution and the increased possibility of doing well in the country, the school experience of parents and older children are factors behind the decision made by parents. Nevertheless, we also find that extended family, even the third generation, has an impact on school choice. CONCLUSIONS, RECOMMENDATIONS AND APPLICABLE VALUE OF RESEARCH: The research presents a perspective that focuses on the educational results of respondents most of whom proved to be successful in their respective fields. The results we found confirm hypotheses from the literature regarding the language choices of different nationalities. The research is a part of a larger project which aims at the exploration the research upon the students attending non‑native language schools.